2013
DOI: 10.1002/uog.11223
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional power Doppler ultrasound in cervical carcinoma: monitoring treatment response to radiotherapy

Abstract: Objectives To investigate, using three-dimensional power Doppler ultrasound (3D-PDU), alterations in cervical intratumoral vascularization during and after radiotherapy. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
1
11
0
6
Order By: Relevance
“…More recently, Huang et al used 3D power Doppler ultrasound for monitoring the response to radiotherapy and to detect tumor recurrence [39]. They found that this technique is useful to assess tumor response during treatment, since responding tumors showed a significant decrease in vascularization, and also it showed a better sensitivity than serum markers to detect recurrence.…”
Section: Ultrasound For Predicting Response To Therapymentioning
confidence: 99%
“…More recently, Huang et al used 3D power Doppler ultrasound for monitoring the response to radiotherapy and to detect tumor recurrence [39]. They found that this technique is useful to assess tumor response during treatment, since responding tumors showed a significant decrease in vascularization, and also it showed a better sensitivity than serum markers to detect recurrence.…”
Section: Ultrasound For Predicting Response To Therapymentioning
confidence: 99%
“…Lower intratumoral PI is associated with higher vascularization and tissue oxygenation distal from the sampling site. Thus, tumor with lower PI should have better response to radiation (Huang et al, 2013). We demonstrate that patients with lower PI demonstrated better response to radiation.…”
Section: Discussionmentioning
confidence: 60%
“…Intratumoral blood flow correlated to several tumor characteristics, such as grade, histology type, volume, and stage. Tumor with poor differentiation, higher volume, and more advance stage present with higher vascularization characterized by decreased RI and PI (Huang et al, 2013;Mangla and Singla, 2015). RI decreases significantly after radiation which indicate decreased perfusion and oxygenation to cervical tissue after radiation (Alcazar et al, 2003;Mangla and Singla, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Terdapat berbagai faktor yang mempengaruhi respons radiasi terutama adalah faktor oksigenasi kanker, dimana pada jaringan kanker yang kaya oksigen maka respons terapi radiasi akan lebih baik karena mekanisme kerusakan DNA melalui pembentukan radikal bebas lebih besar dibandingkan sel yang mengalami hipoksia (Gambar 1). [12][13][14][15][16][17][18][19][20] Oksigen memainkan peran penting pada respons kanker dengan dosis padat terhadap radioterapi. Kanker yang sangat ter-vaskularisasi memiliki pengiriman oksigen lebih banyak dan karena itu, respon yang lebih baik untuk kemoradiasi daripada tumor dengan vaskularisasi minimal.…”
Section: Pendahuluanunclassified
“…Teknik pencitraan fungsional menggunakan USG Doppler dapat menampilkan perfusi jaringan secara in vivo dengan menampilkan perfusi mikro sirkulasi dari lesi dan menggambarkan status oksigenasi secara langsung. [12][13][14][15][16][17][18][19][20] Hasil penelitian sebelumnya menemukan hasil yang berbeda-beda. Terdapat penelitian yang menemukan bahwa kanker dengan vaskularisasi baik, sebagaimana dinilai oleh Transvaginal Colour Doppler sonography (TVCD), memiliki respon yang lebih baik untuk kemoradioterapi dari tumor yang sangat tervaskularisasi.…”
Section: Pendahuluanunclassified